Law Enforcement of Indonesian National Army (TNI) Soldiers with a Progressive Legal Approach - Budi Pramono (Fakultas Hukum Universitas Hang Tuah, 2021)
The implementation of law enforcement in the Indonesian National Army (TNI) is still chaotic due to the sectoral ego of each law enforcement officer so that it is necessary to discuss the concept of law enforcement against soldiers who commit violations using a progressive legal approach conceptual. This research is a normative (doctrinal) legal research with a statutory and conceptual approach. Law enforcement in the Indonesian National Army environment requires the development of the approach that used, one of which uses a progressive legal approach. In progressive legal thinking, the law should be able to give happiness to the people and the nation so that the development of soldier morality is needed. Thinking progressively in law means having the courage to get out of the mainstream of legal absolutism thinking, then placing the law in a relative position. Progressivism does not want to make law a technology that has no conscience, but rather a moral institution, in this case human morality. Good physical development but bad mentality makes the direction of the law go astray.